2017
DOI: 10.1177/1178633717702869
|View full text |Cite
|
Sign up to set email alerts
|

Honey as a Complementary Medicine

Abstract: The beneficial effects of honey on human health have long been recognized. Today, many of those positive effects have been studied to elucidate its mode of action. This review briefly summarizes the best studied features of honey, highlighting it as an appealing alternative medicine. In these reports, the health benefits of honey range from antioxidant, immunomodulatory, and anti-inflammatory activity to anticancer action, metabolic and cardiovascular benefits, prebiotic properties, human pathogen control, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 208 publications
(370 reference statements)
0
94
0
3
Order By: Relevance
“…These beneficial effects of honey are probably mediated through its high phenolic content. According to Alam, Islam, Gan, and Khalil (2014) and Miguel, Antunes, and Faleiro (2017), honeys such as Acacia and thyme promote burn and wound healing due to their anti-bacterial, anti-inflammatory and immunomodulatory effects. Honey delays cancer development and improve the health of the gut by acting as a probiotic agent (Miguel et al, 2017).…”
Section: Honey Colourmentioning
confidence: 99%
See 2 more Smart Citations
“…These beneficial effects of honey are probably mediated through its high phenolic content. According to Alam, Islam, Gan, and Khalil (2014) and Miguel, Antunes, and Faleiro (2017), honeys such as Acacia and thyme promote burn and wound healing due to their anti-bacterial, anti-inflammatory and immunomodulatory effects. Honey delays cancer development and improve the health of the gut by acting as a probiotic agent (Miguel et al, 2017).…”
Section: Honey Colourmentioning
confidence: 99%
“…According to Alam, Islam, Gan, and Khalil (2014) and Miguel, Antunes, and Faleiro (2017), honeys such as Acacia and thyme promote burn and wound healing due to their anti-bacterial, anti-inflammatory and immunomodulatory effects. Honey delays cancer development and improve the health of the gut by acting as a probiotic agent (Miguel et al, 2017). Several studies have shown that honeys from diverse floral sources including Acacia, citrus, rosemary and thyme possess potential anti-cancerous activities (Miguel et al, 2017).…”
Section: Honey Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the lifestyle factors that play an important role in human health, nutrition is key. Recent clinical and epidemiological studies indicate that honey may act as an important mediator of human health [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to resistance against the common antibiotic, researchers are working more on traditional method of treatments [6]. Use of honey is increasing for wound healing, for treatment of hypertension and also in many GIT conditions [7]. This will be an era when there will be no more antibiotic for the treatment of common infections [8].…”
Section: Introductionmentioning
confidence: 99%